Distribution of recent ostracoda in offshore sediment around Pulau Besar, Johor - Ramlan Omar,; Noraswana Nor Faiz, (Universiti Kebangsaan Malaysia, 2010)
The study on distribution of ostracods in offshore sediment was made around Pulau Besar, Johor. A total of 11 stations were chooser. A total of 47 species, both living and dead belonging to 37 genera and 18 families were collected and had been identified. A total of 1063 dead specimens and 932 living specimens of ostracoda were found in the study area. The dominant species was Pistocythereis cribriformis and the dominant family was Trachyleberididae. Family that had the most high species diversity was Trachlyeberididae with 14 species. Several physico-chemical parameters were measured in-situ including temperature, salinity, dissolved oxygen and depth. The values for each of these parameters range from 27.05-30.80oC, 31.20-34.01 ppt, 6.90-11.93 mg/L and 6.60-20.50 m, respectively. For ex-situ physico-chemical parameters such as percentage of organic matter, sand, clay and silt with the range values for each parameter were 1.98-7.58%, 74.87-95.05%, 0.05-24.21% and 0.75-9.74%, respectively. The sediment texture in this study area can be categorized as silty sand, very fine sand, fine sand, medium sand and coarse sand. Shannon-Wiener diversity Index, H(S) was highest at ST 6 station with 2.91 and lowest at ST 11 station with 2.26. The abundance and diversity of ostracod were most related to the character of the sediment. The percentage of silt were positively and significantly correlated with the abundance of ostracods while temperature and percentage of sand are negatively and significantly correlated with benthic ostracod abundance. Other parameters do not show any significant correlation.